Integrating nanomaterials and 3D nano/microfabrication techniques for improved cartilage and bone regeneration - Zhang, Lijie Grace (Henry Stewart Talks, 2015)
Background, Concept model: design of 3D tissue construct, Design of novel nanomaterials for cartilage and bone tissue regeneration, Integrating 3D fabrication techniques and nanomaterials for osteochondral and cartilage tissue regeneration